FAKTOR PRODUK, HARGA, DAN KUALITAS PELAYANAN PADA KEPUTUSAN PEMBELIAN KONSUMEN HISANA FRIED CHICKEN WRINGINANOM - Nila Livia Sari; Yunita Siti Mardhiyyah; Dyah Satiti (Program Studi D4-Manajemen Bisnis, Jurusan Teknik Bangunan Kapal, Politeknik Perkapalan Negeri Surabaya, 2023)
Purchasing decisions are the final goal in marketing a product. Factors that can influence consumer purchasing decisions, including product quality, price, and service quality. The population of this research is the consumers of Hisana Fried Chicken Wringinanom. The sampling technique used is purposive sampling with 100 respondents as the sample. The data collection technique used is a questionnaire and the data analysis method used is multiple regression analysis.The results of data analysisfrom this study indicate that Product, price, service quality variables simultaneously affect on purchasing decisions with F count 69,005 > F table 2,70. While partially the product variable has no effect on purchasing decisions with t count 1.759 < t table 1.985 but the price and quality of purchase variables affect purchasing decisions with t count variable price 2,975 > t table 1,985 and t count variable service quality 8.872 > t table 1,985. It was suggested to improve service quality on Hisana Fried Chicken Wringinanom.